Fixing the Game? Legitimacy, Morality Policy and Research in Gambling - Miller, Rohan; Michelson, Grant (Journal of business ethics, 2013)
It is a truism that some industries are controversial either because the processes employed or the resulting products, for instance, can potentially harm the well-being of people. The controversy that surrounds certain industries can sharply polarise public opinion and debate. In this article, we employ legitimacy theory and morality policy to show how one industry sector (the electronic gaming machine sector as part of the wider gambling industry) is subject to this reaction. We suggest that the difficulty in establishing legitimacy surrounding CSR practices in this sector is related to morality policy, whereby ideology and personal values play important roles in dividing opinion. Thus, gambling is often framed as an activity that is morally and ethically problematic. To show how this can manifest, we examine the veracity of two state-funded studies in Australia used in the development of gambling policy and their subsequent adoption in academic research. We highlight methodological, analytical and reporting issues in these studies that normally should be identified by those using such findings. The significance is that when morality policy and conflict surrounding legitimacy are involved, then it can explain why adherence to normative research standards is potentially lowered. Our theoretical posture leads us to further speculate that the adoption and communication of CSR in electronic gambling will be contested by opponents of the industry.